Credit derivatives design to facilitate loan purchase agreements in the secondary loan market in Thailand. Issue 5 (11th May 2020) - Charoontham, Kittiphod; Kanchanapoom, Kessara
Abstract : Purpose: This paper aims to study a strategic decision of banks in Thailand to signal their types to the market and derive the optimal credit derivatives contract to guarantee their loans and credibly signal their quality under different economic determinants, namely, the maximum credit risk investment constraint, opportunity cost and opaqueness of the credit derivative market. Design/methodology/approach: Contract theory is deployed to derive the expected payoff of different bank types under different economic and financial constraints. Hence, different bank types offer derivatives contracts to signal their loan quality and resell their loans in the secondary loan markets of Thailand. Findings: The optimal derivatives contract is constructed on a basis of asymmetric information when banks have more private information concerning quality of their loans. A digital credit default swap is an optimal derivatives contract to send credible signal when banks are restricted to the maximum investment constraint. Moreover, profit of banks is reduced, as the optimal derivatives contract is more costly when banks are subjected to positive opportunity cost and opacity of the credit derivatives market. These results depict impact of changes of the maximum credit risk investment constraint on Thai credit derivatives market. Originality/value: The optimal credit derivatives design that signifies bank types and facilitates loan purchase agreement has not been studied in Thai secondary loan markets before. In addition, this study provides insights of banks' strategic decisions to signal their types and transfer risk to risk buyers in Thai markets.